Gasphasenumsetzung von Dimethylmaleat zu Tetrahydrofuran : Prozessintensivierung und Kinetik - Marz, Stefan (KIT Scientific Publishing, 2014)
In the present study the single stage gas phase conversation of dimethyl maleate to tetrahydrofuran on Copper/zinc/alumina oxide was investigated. On the basis of kinetic measurements the kinetics was described and options for process intensification, specially the reduction of the hydrogen concentration, was demonstrated.